Microphopagation of Date Palm (Phoenix Dactylifera L.) CV Khadrawy using Tissue Culture Technique - Kackar, N L; Solanki, K R; Joshi, S P (Annals of Arid Zone, 2016)
Small segment of explant (1 cm) from tip of young offshoot (1-2 year) of date palm were cultured on modified Murashige and skoog (1962) medium. Significant reductions in the time required for callus formation (two weeks, and development of plantlets wen: observed in the modified nutrient medium. Developed plantlets were transferred on a modified MS medium containing 2 mg/l each of narhthylacetic acid, naphthoxyacetic acid and benzyl adenine for ,ucce,sful hardening and then transferred to pots. Potted plants became ready for field Iransfer within twomontl1s.